Effect of Parenteral Nutrition-Associated Factors on the Growth of Premature Infants - Kittiyaporn Tongiew ,; Chuleegone Sornsuvit ,; Chanin Jiamsajjamongkhon, (Journal of Pharmacy and Nutrition Sciences, 2020)
Objective: To investigate the factors that affect the growth of preterm infants who receive parenteral nutrition (PN). Methods: A retrospective cohort study was performed in Uttaradit hospital, Thailand, using data collected between January 2012 and July 2016. The main outcome measure was postnatal growth failure (PGF), comprising weight gain rate at 36 weeks, weight at 36 weeks, time to regain birth weight and growth failure at 36 weeks. Results: Eighty preterm infants were included in this study, with a mean gestational age of 32 weeks and birth weight of 1468 grams. Multiple regression analysis indicated that the time to achieve full enteral feeding (r = 0.33, 95% CI[0.01,0.48]) was associated with the weight gain rate at 36 weeks of corrected age, birth weight (r = -0.53, 95% CI[-445.04, -216.70]) was associated with weight at 36 weeks of corrected age, the initial timing of PN (r = -0.24, 95% CI[-4.10, -0.40]), average amount of protein in PN (r = 0.39, 95% CI[0.55, 3.43]) and the initial amount of protein in PN (r = -0.46, 95% CI[-3.19, -1.00]) were associated with the time to regain birth weight, and a birth weight classified as small for gestational age (SGA, OR = 15.90, 95% CI[1.54,164.14]) was significantly associated with growth failure at 36 weeks of corrected age. Conclusions: The results of this study indicate that both nutrition and non-nutrition factors affect PGF in preterm infants who receive PN.